Increasing security of supply for critical medical and pharmaceutical goods in the EU: Lessons from the COVID-19 pandemic - Jan Grumiller; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2021)
This Briefing Paper examines the resilience of the medical product and pharmaceutical global value chains. Based on this assessment, policy recommendations are presented to increase supply security, including measures to improve the resilience of supply chains, and to expand stockpiling. We also highlight that industrial policy measures to promote reshoring should play a more important role, and that coordination on the EU-level is necessary. Given the large differences between products and supply chains within and between sectors, policies need to be tailored to specific products and product groups. Finally yet importantly, repercussions of EU policy on the Global South also need to be taken into account.
Keywords: 330; supply chain resilience; reshoring; pharmaceuticals; medical products; COVID-19